Meningkatkan Kemampuan Bernalar Kritis Peserta Didik Pada Mata Pelajaran PAKBP Melalui Metode PBL Kelas IX SMPN 4 Menyuke - Marta Lea Resti Prana Widya Anka; Timotius Tote Jelahu; Modestus Haryono (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
This research is motivated by the low learning motivation and critical thinking skills of students in the Catholic Religious Education subject at SMPN 4 Menyuke. The use of monotonous teaching methods is one of the main causes for the lack of stimulation for students to think critically. To address this issue, the Problem-Based Learning (PBL) method was implemented as an interactive approach aimed at improving students' critical thinking skills and learning outcomes. This study used classroom action research conducted in two cycles. In cycle I, the observation of critical thinking skills showed that all students were in the "Developing" category with an average class score of 69.0. The most commonly achieved indicator was "Asking questions to clarify information," while the lowest was "Explaining assumptions used in the thinking process." In cycle II, there was a significant improvement with the average class score increasing to 81.1, reflecting the effectiveness of PBL in enhancing students' critical thinking and analysis. Cognitive learning outcomes also improved, where in cycle I most students were in the "Sufficient" category, and only 5 students reached the "Proficient" category with an average score of 78. In cycle II, the average score increased to 85, with several students reaching the "Proficient" category. This improvement between cycles indicates that PBL is effective in enhancing students' cognitive understanding.